Executive control network connectivity strength protects against relapse to cocaine use. (7th September 2016) - McHugh, Meredith J.; Gu, Hong; Yang, Yihong; Adinoff, Bryon; Stein, Elliot A.
Abstract: Cocaine addiction is characterized by notoriously high relapse rates following treatment. Recent efforts to address poor treatment outcomes have turned to potential neural markers of relapse risk. Accordingly, the present study examined resting state functional connectivity (rsFC) within and between three large‐scale cortical networks: the default mode network (DMN), salience network (SN) and executive control network (ECN). All three have been implicated in relapse‐related phenomena including craving, withdrawal and executive control deficits. Forty‐five cocaine‐dependent individuals and 22 healthy controls completed 6‐min resting fMRI scans, The Wisconsin Card Sorting Task, Continuous Performance Test and Cocaine Craving Questionnaire. Cocaine‐dependent individuals completed all measures in the final week of a residential treatment episode. Ten control and 9 abstinent cocaine‐dependent individuals returned for 3–6 month follow‐up scan visits. A group‐level independent component analysis was employed to generate ECN, DMN and SN components. For individuals abstinent up to day 30 post‐treatment ( n = 21), we found enhanced pre‐discharge rsFC between the left ECN and both the right ECN and SN as well as between the right ECN and left ECN. Left ECN rsFC effects remained elevated 3–6 months later among abstinent cocaine‐dependent individuals. Relapse was related to fewer years of education and more years smoking but no other demographic, clinical, treatment and neurocognitive characteristics. Findings suggest that interhemispheric ECN and ECN‐SN connectivity strength may protect against relapse to cocaine use following treatment. These patterns of enhanced interhemispheric network connectivity may reflect a greater capacity to engage executive control processes when faced with opportunities to use cocaine post‐treatment. Abstract : Resting state connectivity was examined in 45 individuals immediately prior to discharge from treatment for cocaine dependence. Connectivity strength within the executive control network and between the executive control network and salience network was found to protect against relapse 30 days post‐treatment. Effects may reflect a greater capacity to engage executive control processes when faced with opportunities to use cocaine.